Experimental verification of the ability to modify existing topical preferences using individually organized unconscious information impact. - Proshutinskiy, Uriy; Dementeva, Nadezhda (Archivos Venezolanos de Farmacología y Terapéutica, 2022)
Introduction: the current study aims to discuss a new method of investigating unconscious perception. The main aim is to analyze the experimental verification of the capability of modifying existing topical preferences utilizing individually organized unconscious information impact. The idea of the experiment was to change the targeted level in subjects' relevant emotional appeal towards its increase to the previously unattractive object. Methods: To meet that aim, a study was carried out involving 60 students from different faculties of Petrozavodsk State University (PSU), 30 girls and 30 boys aged 19 to 23 years. For mathematical processing of results to determine the significance of differences, the Mann-Whitney test, and x2. Results: The results of the second computer procedure of the female sample decided at twentysix women, constituting 86.6% of the group, with significant differences increasing the response to one of four portraits. Conclusion: Women are more prone to changes in actual emotional preferences than men. However, this trend was not statistically validated.